Design experimental of RF controlled beach cleaner robotic vehicle. Issue 1 (December 2020) - Praveen, R; Prabhu, L; Premjith, P; Mohan, Adarsh. K.; Ajayraj
Abstract: The research article on vortex tube, which deals with the operation of statistic parts. The project, tried it best to brief the RF control beach cleaner which is robotic vehicle that helps in cleaning the shores. It helps to collect the Garbage's, plastics etc near the shore. The concept of this project is to find solutions to help the marine life environment that garbage and litter is affecting the environment and everything surrounding it. This machine system is specifically focused to pick up litter from beaches and shores to serve the organizations and volunteers related to this issue. This project can be used in all different shores and beaches which will help organizations to achieve more and clean better with our project's prototype.